2020
DOI: 10.1016/j.psj.2019.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Lyophilization of hyperimmune egg yolk: effect on antibody titer and protection of broilers against Campylobacter colonization

Abstract: Oral administration of antibodies is a promising strategy against various infectious diseases. Previously, it was demonstrated that passive immunization by providing hyperimmune egg yolk through the feed reduces Campylobacter jejuni colonization in broilers. Campylobacteriosis is the most commonly reported bacterial foodborne zoonosis worldwide, and poultry products are the number one origin of these bacteria for human infection. To date, no effective control measures exist to limit Campylobacter colonization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… Shanker et al (1986) discovered that unless C. jejuni was directly injected into albumin, natural colonization did not occur, even when C. jejuni -challenged eggshells were used. In addition, a number of investigations have failed to differentiate the identical genotypes of C. jejuni in parent farms and their chicken offspring ( Petersen et al, 2001 ; Vandeputte et al, 2020 ). The presence of anti- Campylobacter antibodies in the mother reduces both the vertical transmission and proliferation of the bacteria in newly hatched chickens ( Sahin et al, 2001 ).…”
Section: Epidemiology Of Campylobacter In Broiler ...mentioning
confidence: 99%
“… Shanker et al (1986) discovered that unless C. jejuni was directly injected into albumin, natural colonization did not occur, even when C. jejuni -challenged eggshells were used. In addition, a number of investigations have failed to differentiate the identical genotypes of C. jejuni in parent farms and their chicken offspring ( Petersen et al, 2001 ; Vandeputte et al, 2020 ). The presence of anti- Campylobacter antibodies in the mother reduces both the vertical transmission and proliferation of the bacteria in newly hatched chickens ( Sahin et al, 2001 ).…”
Section: Epidemiology Of Campylobacter In Broiler ...mentioning
confidence: 99%
“…In general, eggs are collected weekly, starting 1 wk prior to the first immunization (pre-immune eggs), eggshells are washed or sanitized with 70% ethanol, and stored at 4℃ until further processed for IgY isolation. Lyophilization of egg yolk has also been reported, resulting in an easy-to-mix egg yolk powder with an extended shelf-life[ 45 ].…”
Section: Development and Evaluation Of Egg Yolk-derived Polyclonal Igysmentioning
confidence: 99%
“…Useful information concerning earlier findings on the stability and storage conditions of IgYs has appeared in recent review articles[ 73 ]. Freeze-drying has been used to facilitate long storage of IgYs[ 74 ], though some researchers have reported that freeze-drying may lead to some loss of antigen-binding activity of IgY[ 45 ]. Lyophilization of proteins, including IgYs, induces freezing and dehydration stresses, which may result in protein structural changes or even unfolding[ 75 ].…”
Section: Development and Evaluation Of Egg Yolk-derived Polyclonal Igysmentioning
confidence: 99%
See 2 more Smart Citations